CyberKnife for Recurrent Malignant Gliomas: A Systematic Review and Meta-Analysis - De Maria, Lucio; Terzi di Bergamo, Lodovico; Conti, Alfredo; Hayashi, Kazuhiko; Pinzi, Valentina; Murai, Taro; Lanciano, Rachelle; Burneikiene, Sigita; Buglione di Monale, Michela; Magrini, Stefano Maria; Fontanella, Marco Maria (Frontiers in Oncology, 2021)
Possible treatment strategies for recurrent malignant gliomas include surgery, chemotherapy, radiotherapy, and combined treatments. Among different reirradiation modalities, the CyberKnife System has shown promising results. We conducted a systematic review of the literature and a meta-analysis to establish the efficacy and safety of CyberKnife treatment for recurrent malignant gliomas. We searched PubMed, MEDLINE, and EMBASE from 2000 to 2021 for studies evaluating the safety and efficacy of CyberKnife treatment for recurrent WHO grade III and grade IV gliomas of the brain. Two independent reviewers selected studies and abstracted data. Missing information was requested from the authors via email correspondence. The primary outcomes were median Overall Survival, median Time To Progression, and median Progression-Free Survival. We performed subgroup analyses regarding WHO grade and chemotherapy. Besides, we analyzed the relationship between median Time To Recurrence and median Overall Survival from CyberKnife treatment. The secondary outcomes were complications, local response, and recurrence. Data were analyzed using random-effects meta-analysis. Thirteen studies reporting on 398 patients were included. Median Overall Survival from initial diagnosis and CyberKnife treatment was 22.6 months and 8.6 months. Median Time To Progression and median Progression-Free Survival from CyberKnife treatment were 6.7 months and 7.1 months. Median Overall Survival from CyberKnife treatment was 8.4 months for WHO grade IV gliomas, compared to 11 months for WHO grade III gliomas. Median Overall Survival from CyberKnife treatment was 4.4 months for patients who underwent CyberKnife treatment alone, compared to 9.5 months for patients who underwent CyberKnife treatment plus chemotherapy. We did not observe a correlation between median Time To Recurrence and median Overall Survival from CyberKnife. Rates of acute neurological and acute non-neurological side effects were 3.6% and 13%. Rates of corticosteroid dependency and radiation necrosis were 18.8% and 4.3%. Reirradiation of recurrent malignant gliomas with the CyberKnife System provides encouraging survival rates. There is a better survival trend for WHO grade III gliomas and for patients who undergo combined treatment with CyberKnife plus chemotherapy. Rates of complications are low. Larger prospective studies are warranted to provide more accurate results.